Effect of Application Rate and Timing on Residual Efficacy of Pyraclostrobin in the Control of Pepper Anthracnose - Gao, Y Y (Plant disease, 2020)
Anthracnose is a devastating disease that seriously affects pepper production worldwide. Anthracnose management is currently a major problem because of the widespread and long period of infection of this disease. Therefore, determination of the optimal fungicide application timing is important for controlling anthracnose in a timely manner . In vitro sensitivity tests showed no significant difference in the pyraclostrobin sensitivity of Colletotrichum scovillei collected from 2016 and 2017, with mean half maximal effective concentration values of 0.349 to 0.542 and 0.0475 to 0.0639 mg/liter for the inhibition of mycelial growth and spore germination, respectively. Fungicide application initiated at the full-bloom stage could significantly delay anthracnose disease onset, decrease anthracnose incidence and development (23.67 to 89.80%), and increase pepper yield by 10.7 to 29.2%. In addition, the application dosage was decreased by >50%. BF-500-3, the main metabolite of pyraclostrobin, was detected in pepper fruit and exhibited high inhibitory activity against C. scovillei. The final residues of all fungicides at different application timing were below maximum residue limits. Moreover, structural equation modeling indicated that application timing plays the most important role in anthracnose disease inhibition. The tank mixtures of pyraclostrobin with tebuconazole and fludioxonil showed more satisfactory efficacy (69.87 to 78.36%) against anthracnose than did pyraclostrobin alone under field conditions. This study is the first to determine the best fungicide application timing for anthracnose management. These results establish the basis for sustainable development of the pepper industry